2011
DOI: 10.3233/asy-2011-1054
|View full text |Cite
|
Sign up to set email alerts
|

On semi-classical questions related to signal analysis

Abstract: This study explores the reconstruction of a signal using spectral quantities associated with some self-adjoint realization of an h-dependent Schrödinger operator −h 2 d 2 dx 2 − y(x), h > 0, when the parameter h tends to 0. Theoretical results in semi-classical analysis are proved. Some numerical results are also presented. We first consider as a toy model the sech 2 function. Then we study a real signal given by arterial blood pressure measurements. This approach seems to be very promising in signal analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…This is achieved by choosing a large value of the parameter h to minimize N h , and iteratively lowering it to increase N h to include more eigenfunctions until the noiseless spectrum s h is accurately reconstructed. This is in agreement with the properties of the eigenfunctions ψ ( f ), where it has been shown that the n th squared eigenfunction ψnh2(),f has n wells, implying that the first squared eigenfunction ψ1h2(),f is represented by a single well function localized at its maximum, the second squared eigenfunction ψ2h2(),f has two wells, and so on . By analogy, one can see that the squared eigenfunctions with low n h values represent, in a broad manner, the profiles of the peaks of the spectrum, whereas the functions with high n h values characterize more the fine details of these profiles.…”
Section: Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…This is achieved by choosing a large value of the parameter h to minimize N h , and iteratively lowering it to increase N h to include more eigenfunctions until the noiseless spectrum s h is accurately reconstructed. This is in agreement with the properties of the eigenfunctions ψ ( f ), where it has been shown that the n th squared eigenfunction ψnh2(),f has n wells, implying that the first squared eigenfunction ψ1h2(),f is represented by a single well function localized at its maximum, the second squared eigenfunction ψ2h2(),f has two wells, and so on . By analogy, one can see that the squared eigenfunctions with low n h values represent, in a broad manner, the profiles of the peaks of the spectrum, whereas the functions with high n h values characterize more the fine details of these profiles.…”
Section: Theorymentioning
confidence: 99%
“…The SCSA method, pioneered as a classification method to discriminate between pathological and control patients in arterial blood pressure data analysis, [17][18][19] has been theoretically evaluated as a de-noising technique in biomedical signal processing. 20,21 The method employs the discrete spectrum of the Schrödinger operator to decompose the input signal into a set of squared eigenfunctions, with shapes derived from the potential function of the operator.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations